2001
DOI: 10.1111/j.1600-0781.2001.170604.x
|View full text |Cite
|
Sign up to set email alerts
|

Single dose radiation is more effective for the UV‐induced activation and proliferation of melanocytes than fractionated dose radiation

Abstract: Purpose: To establish whether the effect of fractionating radiation modifies the effects of ultraviolet (UV) radiation on epidermal melanocytes, we compared the clinical and histological effects of single high dose radiation against repeated intermediate to low dose radiation on epidermal melanocytes. Methods: Three minimal erythema UV doses (MED) were administered to three sites on the buttocks of healthy volunteers. One site was irradiated with 0.5 MED UV every day for 6 consecutive days, another site was ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Thus, it was established by partial irradiation of benign nevi in human skin that a single high UV dose showed a high efficacy in inducing proliferative responses, but a high dose fractionated to a suberythemal level did not (138). Similar results were found by counting numbers of stained normal melanocytes in the epidermis, but there was notably no consistency in the fold increase between the different stains used (139). In a recent study we found similar results concerning the effects of a high single versus fractionated dose on the proliferative response of melanocytes in hairless mice (van Schanke et al, J.…”
Section: Effect Of Uv Irradiation On Melanocytes In the Skinsupporting
confidence: 71%
See 1 more Smart Citation
“…Thus, it was established by partial irradiation of benign nevi in human skin that a single high UV dose showed a high efficacy in inducing proliferative responses, but a high dose fractionated to a suberythemal level did not (138). Similar results were found by counting numbers of stained normal melanocytes in the epidermis, but there was notably no consistency in the fold increase between the different stains used (139). In a recent study we found similar results concerning the effects of a high single versus fractionated dose on the proliferative response of melanocytes in hairless mice (van Schanke et al, J.…”
Section: Effect Of Uv Irradiation On Melanocytes In the Skinsupporting
confidence: 71%
“…In contrast, the onco‐H‐ras‐transgenic mice did not develop melanomas spontaneously, but the albinos among them did on chronic UV exposure at an adult age (>3 weeks old, exposures twice a week for 38 weeks) (152). This striking difference between the two models draws attention to the transgenes (perhaps the number of copies per cell) and more in particular to their respective promoters: mt is normally responsive to metal‐toxic, oxidative and (UV) radiation stresses in a wide variety of cells (158–160), whereas the tyr response to such stresses is limited to melanocytes (139). Furthermore, the reaction of melanocytes in the mt‐Hgf model requires the expression of Met, which is not present on melanocytes in adult human skin (75) (it is, however, present on melanocytes in culture [161], which may indicate that Met expression might be upregulated under stress, e.g.…”
Section: Genetically Modified Mouse Models Of Inducible Melanomamentioning
confidence: 99%
“…Studies of melanocyte proliferation after UV exposure have produced divergent results (Tables II and III). Studies supporting melanocyte proliferation (Table ) found an increased number of melanocytes, after between 4 days and 6 months of UVA or UVB exposure.…”
Section: Building a Working Model Of Melanocyte Repopulation In Vitilmentioning
confidence: 99%
“…Studies supporting melanocyte proliferation (Table ) found an increased number of melanocytes, after between 4 days and 6 months of UVA or UVB exposure. The vast majority of studies observed an increased number of melanocytes in the epidermis, while a few observed melanocyte proliferation in the hair follicle ORS . The hypothetical mechanisms by which UV light stimulates melanocyte proliferation include direct effects on melanocytes or their stimulation by keratinocyte‐derived factors: ET‐1, SCF, bFGF, and α‐MSH (Fig.…”
Section: Building a Working Model Of Melanocyte Repopulation In Vitilmentioning
confidence: 99%
“…This suggests that not only the discussed relation but also additional parameters must be considered. This is first the intensity-dependent formation of the erythema at a given dose, 25 and second the photoaugmentation. 26 A detailed discussion of these influences will be performed if the number of the investigated sunscreens is enlarged.…”
Section: Parameter Dependence Of the Relation Universal Sun Protectiomentioning
confidence: 99%